2020
DOI: 10.1038/s41598-020-65796-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different straw biochars on soil organic carbon, nitrogen, available phosphorus, and enzyme activity in paddy soil

Abstract: Biochar is widely used as a soil amendment. Enzyme activity is an important factor that reflects soil metabolic activity, and is involved in biochemical processes such as organic matter decomposition and nutrient cycling in soils. However, the effects of biochar prepared for different straw materials on soil enzyme activity and soil nutrients are rarely studied. Through pot experiments, the effects of different straw (wheat, rice, maize) biochars (obtained by pyrolysis at 500 °C) on soil organic carbon, nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(55 citation statements)
references
References 52 publications
(29 reference statements)
5
39
0
1
Order By: Relevance
“…The higher the amount of biochar applied, the higher the content of organic carbon, which is consistent with the conclusion of [40]. The increase in the organic carbon content may be due to the high organic carbon content in biochar [29]. The CSB treatment increased the organic carbon content more significantly than the BSB treatment.…”
Section: Impacts On Soil Nutrients After Different Straw Biochar Applsupporting
confidence: 86%
See 3 more Smart Citations
“…The higher the amount of biochar applied, the higher the content of organic carbon, which is consistent with the conclusion of [40]. The increase in the organic carbon content may be due to the high organic carbon content in biochar [29]. The CSB treatment increased the organic carbon content more significantly than the BSB treatment.…”
Section: Impacts On Soil Nutrients After Different Straw Biochar Applsupporting
confidence: 86%
“…The ability of soil to store and supply phosphorus can be reflected by the available phosphorus content, and available phosphorus in soil is also an index of the soil phosphorus level [29]. The results of this experiment showed that the addition of banana straw biochar and cassava straw biochar significantly increased the available phosphorus content and effectively improved the acidity of soil over a long period.…”
Section: Impacts On Soil Nutrients After Different Straw Biochar Applmentioning
confidence: 89%
See 2 more Smart Citations
“…It is widely regarded as a promising way for organisms to inhibit soil-borne pathogens and promote plant growth [12,13]. The composition and diversity of the soil microbial community is very important to soil health, and soil enzyme activity is the index of soil biological activ-ity [14,15]. Increasing continuous cropping years results in a decrease in soil nutrients and enzyme activity [16].…”
Section: Introductionmentioning
confidence: 99%